Optimizing English Language Training Through British Council Learn English Kids in Banthamaprao School Thailand - Maulana, Aditia Hendri; Syah Putra, Aidil; Rohim, Abdul (LOSARI DIGITAL, 2024)
This community service aimed to improve the English skills of students at Ban thama prao School in Thailand. They used the British Council’s Learn English Kids website. The program lasted four weeks and used technology-based learning for teachers and students. Starting with an introduction to the web, the activities continued with classroom learning implementation, evaluation, and reflection. The results of the program showed that students significantly improved their reading skills and increased their motivation to learn. In addition, teachers became better at using technology as a learning tool, despite barriers to internet access and technological devices. Recommendations include improving the technology infrastructure and ongoing training for teachers to ensure the sustainability of the program.